Plausible mechanisms in malignisation of non-habit related chronic nonhealing traumatic ulcers of oral cavity - Deepak Pandiar; Reshma Poothakulath Krishnan (Wolters Kluwer Medknow Publications, 2024)
Chronic nonhealing ulcers of the oral mucosa and lateral tongue, in particular, can transform into invasive oral squamous cell carcinoma (OSCC). Sometimes these ulcers do not heal even after the removal of the etiological agent that actually initiated these lesions, something similar to what happens in "neoplasia." Numerous factors have been postulated in the literature; however, the exact mechanism remains unclear. We hereby would suggest few plausible factors that could be considered for future studies to shed light on some untapped territories in the pathogenesis of OSCC arising from chronic nonhealing traumatic ulcers in purview of chromoanagenesis and the concepts of "quantum entanglement and coherence."